2015
DOI: 10.1111/codi.12975
|View full text |Cite
|
Sign up to set email alerts
|

The results of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in 1200 patients with peritoneal malignancy

Abstract: A centralized approach facilitated high volume experience in a single centre with an increase in the completeness of surgical excision rates and a reduction in mortality and morbidity over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 28 publications
4
49
1
5
Order By: Relevance
“…The authors concluded that the 10-year OS rate after CRS and HIPEC was more than 63%. Moran et al [24] have just recently shown a 5-year OS rate of 84% in patients with appendiceal tumours and PMP who had complete cytoreduction. In our cohort, the 5-year OS for patients with PMP was only 62%.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the 10-year OS rate after CRS and HIPEC was more than 63%. Moran et al [24] have just recently shown a 5-year OS rate of 84% in patients with appendiceal tumours and PMP who had complete cytoreduction. In our cohort, the 5-year OS for patients with PMP was only 62%.…”
Section: Discussionmentioning
confidence: 99%
“…Moran et al [13] have reported a 5-year survival rate of 84% after complete resection for patients with appendiceal cancer. In the present study, the 5-year survival rate for patients with appendiceal cancer was 70.0%, regardless of the cytoreduction score.…”
Section: Discussionmentioning
confidence: 99%
“…In lower gastrointestinal tumors including appendix cancer, colon cancer, and rectal cancer, CRS can be beneficial if the PCI is low and the morphology of the PSM is mucinous. Especially in mucinous PSM, even patients with a high PCI are accepted for CRS [10].…”
Section: Introductionmentioning
confidence: 99%